Intracellular Recording of Cardiomyocytes by Integrated Electrical Signal Recording and Electrical Pulse Regulating System - Liu, Zhengjie; Xu, Dongxin; Fang, Jiaru; Xia, Qijian; Zhong, Wenxi; Li, Hongbo; Huang, Zhanyun; Cao, Nan; Liu, Xingxing; Chen, Hui-Jiuan; Hu, Ning (Frontiers in Bioengineering and Biotechnology, 2021)
The electrophysiological signal can reflect the basic activity of cardiomyocytes, which is often used to study the working mechanism of heart. Intracellular recording is a powerful technique for studying transmembrane potential, proving a favorable strategy for electrophysiological research. To obtain high-quality and high-throughput intracellular electrical signals, an integrated electrical signal recording and electrical pulse regulating system based on nanopatterned microelectrode array (NPMEA) is developed in this work. Due to the large impedance of the electrode, a high-input impedance preamplifier is required. The high-frequency noise of the circuit and the baseline drift of the sensor are suppressed by a band-pass filter. After amplifying the signal, the data acquisition card (DAQ) is used to collect the signal. Meanwhile, the DAQ is utilized to generate pulses, achieving the electroporation of cells by NPMEA. Each channel uses a voltage follower to improve the pulse driving ability and isolates each electrode. The corresponding recording control software based on LabVIEW is developed to control the DAQ to collect, display and record electrical signals, and generate pulses. This integrated system can achieve high-throughput detection of intracellular electrical signals and provide a reliable recording tool for cell electro-physiological investigation.